Bank Governance - Ard, Laura; Berg, Alexander (World Bank, Washington, DC, 2012)
Principles of good governance have been a major component of international financial standards and are seen as essential to the stability and integrity of financial systems. Over the past 10 years much energy and attention have gone to improving the ability of company boards, managers, and owners to prudently navigate rapidly changing and volatile market conditions. So, how to explain the events of 2007-08? Many of the recent problems can be traced to flawed implementation of good principles and to behavior prompted by increasingly short-term performance horizons.